Prevalence of ‘at risk’ under five children in a rural area of central India: a cross sectional study - Junaid, Mohd; Deoke, A. R. (International Journal Of Community Medicine And Public Health, 2018)
Background: Children constitute the most vulnerable section of the community. The health status of children serves as sensitive indicator of overall health of entire community. The major causes of deaths in the age group 0-5 years are preventable. At Risk group is a group of individuals in whom the frequency of risk factors is more than the other groups. It is therefore necessary to identify particularly those ’At Risk’ and provide them with efficient paediatric services, because it is these ’At Risk’ babies, which contribute so largely to perinatal, neonatal and infant mortality. Methods: A community based cross sectional study was carried out in a rural area of Nagpur during period of December 2010 to May 2012 to identify prevalence of At Risk under five children and associated demographic, socioeconomic and environmental factors. Sample size taken was 400. By systematic sampling method every 14th house was selected for the study. Epi info software was used for analysis. Results: In the study we found that the prevalence of ‘At Risk’ children were 70.5%. A total of 71.6% male children were ‘At Risk’ as compared to 68.9% female children. Significant association of ‘At Risk’ children was found with education of parents, type of family, socioeconomic status, housing, overcrowding and ventilation. Conclusions: Special provisions of health care facilities for under five children, need based training to the health care providers and necessary information, education & communication campaigns are need of the hour to bring down infant morbidity and mortality.